Finite element study of acetabular cup contact region for Total Hip Replacement (THR) / Muhammad Faris Abd Manap ...[et al.] - Abd Manap, Muhammad Faris; Shuib, Solehuddin; Romli, Ahmad Zafir; Ahmed Shokri, Amran (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Revisions of total hip replacement are caused by many factors. Dislocations, edge-loading and excessive contact pressure at the articulate surface of the acetabular component are among the factors of Total Hip Replacement (THR) failure which required revision. This study aims to simulate the acetabular components for THR with various parameters that may improve the implant lifespan in mechanical aspect. A 3D model of acetabular components is imported into ANSYS WORKBENCH V15 with a different acetabular cup orientation and different femoral head size. Meanwhile, other component parameters at acetabular region are maintained with respect to femoral head size for comparison failure analysis studies. The results showed an increasing of femoral head size diameter from 28mm to 36mm at all selected orientations; the Contact Pressure will reduce by 45% and will improve the Von Mises Stress of about 32%. The Total Deformation value has also improved by 48%. A new parametric study was done by considering an anteversion angle (β). This result indicates that bigger head and even anteversion angle (β) included may also improve the longevity of the prosthesis and boost the articulate motion between the head and acetabular cup. The pressure was distributed evenly at the inner side of the acetabular cup; thus, reduced the excessive contact pressure at the superior region.